Sustainability entrepreneurship education in developing countries: A case of selected universities in the East African Communities - Kidere, Flaura; Mkwizu, Kezia Herman (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2023)
Sustainability Entrepreneurship Education (SEE) as a concept has received less attention from scholars in developing countries. However, the increased call for use of a sustainability entrepreneurship approach to enhance sustainable development in various projects is increasingly becoming a necessity. This situation calls for consideration of how entrepreneurship education should be delivered, particularly regarding sustainability. Clearly, this would be crucial for the university education system which plays a key role in shaping philosophical underpinnings. In expanding the scope of the phenomenon of sustainability from an entrepreneurship education perspective, this study was motivated to explore SEE with a focus on Universities in the East African Community (EAC). The main objective was to establish the existence of a SEE curriculum in selected universities in the EAC. This paper combines desktop review, quantitative and qualitative methods with the application of descriptive statistics and content analysis. The findings show that management and entrepreneurship lecturers commonly defined SE Curriculum (SEC) as an entrepreneurship education that considers the social, economic, and environmental implications within its context. However, SE curriculum (SEC) is not developed. The outcome implies that there is a need to develop SEC in universities. The recommendation is to improve the entrepreneurship education programs in developing countries.